PERSEPSI MASYARAKAT TERHADAP PELAKSANAAN GUSARAN DI DESA SUKACITA KABUPATEN CILACAP - Ayuningsih, Iis; Martono, Nanang; Baharuddin, Nalfaridas (Jurnal Sains Riset, 2024)
This research aims to describe the perceptions of the Sukacita Village community regarding the implementation of gusaran. Gusaran is a tradition of filing girls' teeth to mark the transition from childhood to adulthood. This research uses qualitative methods. Data collection methods include observation, interviews and documentation. The sampling technique uses purposive sampling. Data analysis techniques use interactive analysis methods including data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that there are people who have various meanings regarding perceptions so that there are some community groups who still implement them and there are also those who do not. Some people still carry out gusaran because they think that gusaran is a hereditary tradition that has existed since the time of their ancestors which must be guarded and preserved so that it does not disappear. Meanwhile, some people think that anger is no longer relevant in the current era of modernization because there has been a change in mindset among people who no longer believe in existing myths.